Soil and foliar zinc application for enhancing grain zinc content of aromatic rice genotypes grown on zinc deficient and sufficient soil - SINGH, KHUSHDEEP; VERMA, GAYATRI; MANCHANDA, J. S. (Journal of Soil and Water Conservation, 2020)
To improve and enhance the quality of aromatic rice in zinc deficient soils, application of zinc (Zn) fertilizers is an important strategy. The field experiment was conducted in soils with deficient and sufficient zinc to compare the soil and soil plus foliar Zn application in improving grain Zn concentration and bioavailability in basmati rice. The experiment was laid out in a split plot design with two basmati rice varieties as main plot treatments and seven zinc fertilization treatments as sub plots with three replications. Results of the study indicated that Zn concentration in basmati rice grain and straw increased significantly with increasing zinc levels in soil applied zinc treatments however; more effective increase was recorded in soil plus foliar Zn applications. Increase in Zn levels from 3.12 to 12.5 kg Zn/ha recorded increased grain yield i.e. 29.61, 31.51 and 33.59 q/ha which accounts to 6.7, 13.5 and 21.1 per cent increase over control, respectively in zinc deficient soil. Pusa Basmati 1121 proved better than Punjab Basmati 2 in realizing grain yield. In contrast, soil plus foliar zinc application treatments recorded an increase of 43% and 48% over soil zinc application. Zn uptake was also higher in soil plus foliar zinc application treatments. Soil plus foliar zinc in comparison to soil applied zinc was more effective in improving grain zinc content of aromatic rice varieties grown in zinc deficient and sufficient soil.